Depositional Environments and Archeological Site Formation in the Cypress Hills, Southeastern Alberta - Robertson, Elizabeth (Géographie physique et Quaternaire, 2002)
AbstractPrevious research on the Cypress Hills of southeastern Alberta and southwestern Saskatchewan suggests that they have experienced a dynamic history of Holocene landscape change. In particular, the meltwater channels flanking the Cypress Hills appear to have experienced intermittent deposition of sediment transported from upslope alternating with episodes of landscape stability and soil formation. This pattern favours the formation of archeological sites containing multiple stratigraphically discrete occupations, an important characteristic because the geomorphic processes necessary to create such interpretively valuable sites are rare across much of the Northern Plains. Furthermore, the rich resources offered by the Cypress Hills suggest that they were attractive to past human groups, a feature that enhances the prospects for such sites. This paper discusses a study designed to investigate the geomorphic history of the meltwater channels and to identify buried archeological sites in these channels. The preliminary results of this study confirm that the channels have experienced a cyclical pattern of stability and deposition favourable to the stratified burial of cultural remains. Moreover, this study has recovered archeological material from numerous locations, strongly suggesting that the meltwater channels represent an excellent environment for the formation of high-quality sites with multiple discrete cultural layers.